Optimalisasi Majelis Taklim Muslimah Terhadap Implementasi Islamic Parenting dalam Mencegah Pergaulan Bebas di Kabupaten Sorong - Sudirman; Fardan Abdillah M; Indria Nur; Andi Ahriani; Fitri Siyami (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This thesis discusses the extent of optimizing the taklim council in providing training and learning to the congregation and the implementation of Islamic parenting in preventing promiscuity in Sorong district. This study uses qualitative research that is descriptive so that data will be presented based on the results of interviews, direct observations, and documentation studies to obtain clear data. In addition, this research method also uses a qualitative approach with case studies, where the researcher will investigate in detail and in depth how the Taklim Council functions as a means to convey the principles of Islamic parenting and how it affects the behavior and social interaction of adolescents in overcoming promiscuity. The results of this study show that: (1) The implementation of activities in the taklim council runs optimally in improving literacy in reading the Qur'an and instilling religious values for the congregation who participate in the activities of the Muslim taklim council. However, the implementation of training, especially the provision of materials related to parenting or Islamic parenting, is not optimal, so it must be considered again and improved again the provision of tausiyah or lectures related to childcare in Islam. (2) The implementation of Islamic parenting has been carried out by the congregation based on the knowledge and awareness of the congregation in order to form the character of children based on sharia and Islamic values. (3) Cases of promiscuity that befell children are still found in the midst of the congregation of the taklim council even though only one or two children are involved. And the incident cannot be blamed on one party alone. However, there needs to be reflection and improvement both for the child concerned, his parents, and also the taklim council in the village.